Sabiaceae endémicas del Perú - León, Blanca (2006)
The Sabiaceae are represented in Peru by two genera and 19 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all trees. Here we recognize four endemic species in the genus Meliosma. These endemic species are found in Very Humid Montane Forests region, between 1600 and 2550 m elevation. Three species have been recorded within Peru’s protected areas system.